Productivity analysis of LHD equipment using the 'Five State Markov Model' - Gupta S.; Agrawal A.K.; Agarwal R. (My University, 2025)
Five State Markov Model is a standard way for the productivity analysis of LHD equipment. The basic modeling concept of discrete and continuous markov models was given by Billinton et al [1]. Productivity analysis of mining systems using Markov chain considering only two states for equipment that is an operating state and a non-operating or failed state. LHD loading equipment consist five distinct states, which includes operational (o), failure (f), maintenance (m), degraded (d), and idle state (i) in a mine. The idle state of the LHD are functionally capable to perform its ststed duty. The degraded state of equipment occurs when the equipment performance degraded below some threshold value defining normal designed performance. It has been observed that LHD can transist from its opeartional sate 'o' to degraded state 'd' but cannot transit back to from state 'd' to state 'o' again without having an in-between transition to maintenance state 'm' or a repair state 'f'.